Development of a Sustainable Professional Model for Sports Graduates Based on Future Problem Solving Skills to Support Individual Productivity - Arief Darmawan; Sapto Adi; Moh. Fathur Rohman; Tatok Sugiarto; Novita Sari, Zihan; Nugroho Sigit, Cahyo; Priyohutomo, Ahadi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2024)
Everyday life requires a lot of expenses. Of course, this must be balanced with maximum income. So productivity is very important to achieve goals. Human resource factors in an agency play an important role because they play a role in planning and implementing factors in realizing goals. Individual productivity is one of the factors that can influence success in an organization. This concerns individual development in terms of knowledge and skills in doing something, especially for sports graduates. The method in this service is in stage 1 analyzing the preparedness of the sports master's students' environment towards graduation, analysis of individual career development training needs, stage 2 model design training, validation of the model plan developed, revision of the initial model design which has been validated, stage 3 model testing which was developed, revised the model based on feedback and findings from implementation results, implementation model stage 4, training/dissemination stage 5. The results of the service implementation were carried out smoothly so that it could be implemented well. With this dedication, it is hoped that the audience will not only gain knowledge but also be able to design their own profession or career targets for the next few years